Penerapan Sistem Penjualan Cash Dan Credit Card Dalam Kaitannya Dengan Member Card Discount - Budianto, Enjang Tachyan; Marpaung, Annaria Magdalena; Kenshy, Indrie (Jurnal Ilmiah Ranggagading (JIR), 2011)
Selling is a very important sector, so many ways are often taken to improve companyâs selling system, starting from the traditional to the modern one. Along with the rapid development of technology, many companies utilize technology to improve the companyâs system.They look at promising point from the empowerment of technology. The purpose of this study is to analyze the selling system at a company carrying out the selling process of goods. In the company there are two ways of selling, sales in cash and sales using credit card. This analysis was conducted to find out whether the system adopted in the company works well, where the system is reliable to assess the accuracy of the inventory. The company issues card member to customers, so that the writer also analyzes the system of sales in cash and sales using credit card in its connection with the use of membership cards. This research was done at PT X located in Bogor, a company thatâs engaged in retail sales. From the research done at PT X, it can be known that the system of sales in cash and sales using credit card were done well. For the sales using credit card, the company reported its revenueafter thereâs revenue in bank appointed byretail sales company, so the accounting department has to perform bank reconciliation regularly and makes reporting properly.